2021
DOI: 10.1167/tvst.10.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Increased Systemic C-Reactive Protein Is Associated With Choroidal Thinning in Intermediate Age-Related Macular Degeneration

Abstract: Purpose C-reactive protein (CRP) and decreased choroidal thickness (CT) are risk factors for progression to advanced age-related macular degeneration (AMD). We examined the association between systemic levels of CRP and CT in patients with intermediate AMD (iAMD). Methods Patients with iAMD in the Colorado AMD Registry were included. Baseline serum samples and multimodal imaging including spectral domain–optical coherence tomography (SD-OCT), fundus photography, and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…While choroidal thickness was found here to be increased in early/intermediate patients with higher CRP levels, previous research studies have related increased CRP levels with thinner choroid ( 25 ), thus supporting a role for CRP as an inflammation biomarker of AMD progression. However, such studies did not differentiate among AMD stages and could be explained by the presence of atrophy or previous treatment in advanced AMD.…”
Section: Discussionsupporting
confidence: 74%
“…While choroidal thickness was found here to be increased in early/intermediate patients with higher CRP levels, previous research studies have related increased CRP levels with thinner choroid ( 25 ), thus supporting a role for CRP as an inflammation biomarker of AMD progression. However, such studies did not differentiate among AMD stages and could be explained by the presence of atrophy or previous treatment in advanced AMD.…”
Section: Discussionsupporting
confidence: 74%
“…Although much of the understanding of this process has been focused on complement and specifically on CFH mutations, we believe that complement does not function in isolation in immune-mediated responses and that other soluble mediators as well as cellular components of inflammation may be important. For example, C reactive protein (CRP) has also been shown to be related to AMD development and we have shown that increased serum CRP is correlated with decreased choroidal thickness in iAMD (14). The final pathology in AMD is local damage to the RPE and outer retina, however the systemic inflammatory milieu may alter the local inflammatory responses.…”
Section: Discussionmentioning
confidence: 93%
“…In one study, reduction in the choriocapillaris complex thickness was significantly associated with AMD progression over 5 years of follow-up ( p < 0.001): a thickness of < 10.5 µm was associated with a high probability of progression, whereas a thickness of > 10.5 but < 20.5 µm was associated with moderate probability [ 87 ]. However, the relationship between choroidal thickness and AMD status is affected by several other factors, such as axial length, age, and possibly the presence of RPD, which complicates the reported associations [ 86 , 88 ].…”
Section: Structural Biomarkersmentioning
confidence: 99%
“…Interestingly, a combination of elevated CRP and the CC (Y402H) genotype in the CFH gene resulted in a superadditivity of risks, with an OR of 19.3 (95% CI 2.8–134) for late AMD and 6.8 (95% CI 1.2–38.8) for AMD progression [ 146 ]. In another study, CRP was significantly associated with choroidal thinning in patients with iAMD ( p = 0.01) [ 88 ].…”
Section: Structural Biomarkersmentioning
confidence: 99%